Call the experts: identifying stakeholders in the long-term care of youth with hypospadias - Bhatia, Vinaya P.; Ebert, Kristin; Cannon, Shannon; Farhat, Walid A.; Brown, Heidi W.; Mahoney, Jane; Hilliard, Marisa E.; Penniston, Kristina L. (Frontiers in Pediatrics, 2024)
Long-term follow-up for individuals with hypospadias remains a critical area of need, yet evidence-based guidelines for such follow-up are lacking, and the role for involvement of relevant experts is not yet established. Using our Hypospadias-specific Health-Related Quality of Life Conceptual Framework and a subsequent qualitative study of pre-pubertal males and parents of males with hypospadias, we had identified potential priorities for long-term follow up of youth with hypospadias. Using thematic codes from our patient and parent interviews, we searched PubMed for relevant articles and identified the specialties represented by all the authors of these articles. Our search strategy revealed consistent expertise across HRQOL themes and subthemes, including pediatric and adult urology, health psychology, psychiatry, endocrinology, genetics, and social work. Communication experts, as well as patients and families, were also represented in our literature search. Using these findings, we compiled a comprehensive list of potential stakeholders to inform the development of holistic care guidelines for individuals with hypospadias. By engaging these stakeholders, we aim to develop consensus-based, long-term follow-up guidelines and tools to address the evolving physical and psychosocial needs of people with hypospadias over a lifetime. Use of qualitatively-derived thematic codes to search for relevant literature is an accessible approach for identifying relevant stakeholders. These findings underscore the importance of involving diverse, multidisciplinary expertise to ensure comprehensive, patient-centered care in complex genitourinary conditions.